2004
DOI: 10.1002/ppul.20139
|View full text |Cite
|
Sign up to set email alerts
|

Use of laryngeal mask airway in flexible bronchoscopy in infants and children

Abstract: In the past two decades, flexible bronchoscopy (FB) has gained increasing popularity among pediatric pulmonologists. The objective of this study was to review our experience with pediatric flexible bronchoscopy over the past 15 years, with special focus on route of bronchoscopy. This is a retrospective study. We reviewed our pediatric FB procedures performed at the University of Michigan, Mott Children's Hospital, from 1988-2003. The study included 1,947 procedures in 1,548 patients, with a mean of 1.3 procedu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
27
1
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 23 publications
3
27
1
4
Order By: Relevance
“…For instance, the LMA TM has been used for radiotherapy, 5 magnetic resonance imaging, 6 fibreoptic bronchoscopy, 7 and upper gastrointestinal endoscopy. 8 Its relative stability combined with the ease of respiratory monitoring and the relative lack of airway complications are distinct advantages in these remote locations.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, the LMA TM has been used for radiotherapy, 5 magnetic resonance imaging, 6 fibreoptic bronchoscopy, 7 and upper gastrointestinal endoscopy. 8 Its relative stability combined with the ease of respiratory monitoring and the relative lack of airway complications are distinct advantages in these remote locations.…”
mentioning
confidence: 99%
“…Here the LMA TM has proven to be invaluable both as a rescue airway device in the child with a difficult airway and as a conduit for fibreoptic bronchoscopy and endotracheal intubation. 7 Consequently, the LMA TM has a role in both anticipated and unanticipated difficult airways, and it now features in pediatric difficult intubation algorithms. 9 Even if tracheal intubation is difficult in a child, it must be remembered that the airway is often easy to manage with an LMA TM .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nussbaum et al [9] studied FB via the LMA in a group of children and concluded that the procedure had been well-tolerated in them and that no complication emerged. Naguib et al [2] demonstrated in 1947 procedures that FB through the LMA rendered the lowest rate of overall procedure-related complications when compared to other routes (nasal or endotracheal entubation). The LMA may complicate the assessment of the upper airway abnormalities such as laryngomalacia as a disadvantage.…”
Section: Discussionmentioning
confidence: 99%
“…No certain contraindications for bronchoscopy were noted [1]. The laryngeal mask airway (LMA) has been used since 1983, and the use of bronchoscopy via the LMA of infants and children has increased with the availbility of smaller sizes of the LMA [2]. We performed FB with a 3.7 mm bronchoscope via the LMA in a 75-day-old 1910 g premature baby with atelectasis.…”
Section: Introductionmentioning
confidence: 99%